2017
DOI: 10.1001/jamaneurol.2017.0892
|View full text |Cite
|
Sign up to set email alerts
|

Association of Longitudinal Cognitive Decline With Amyloid Burden in Middle-aged and Older Adults

Abstract: IMPORTANCE Presently, the clinical standard for reporting the results of an amyloid positron emission tomography scan is to assign a dichotomous rating of positive or negative for the presence of amyloid. In a 4-year longitudinal study, we investigated whether using a continuous measure of the magnitude of baseline amyloid burden would provide valuable information about the rate of future cognitive decline over the subsequent 4 years compared with a dichotomous measure in middle-aged and older adults.OBJECTIVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 40 publications
8
69
2
1
Order By: Relevance
“…Consistent with previous reports [4–6], we found that higher cerebral amyloid deposition at baseline predicted longitudinal cognitive decline; however, the individual rate of change in amyloid did not. Xiong et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports [4–6], we found that higher cerebral amyloid deposition at baseline predicted longitudinal cognitive decline; however, the individual rate of change in amyloid did not. Xiong et al.…”
Section: Discussionsupporting
confidence: 91%
“…Future research should also directly analyze a sporadic AD cohort and include subgroup analyses for age and ethnic groups to evaluate whether or not our findings replicate. Second, our cognitive composite score is composed of tests that are different from those used in previous studies [4–9]; therefore, caution is needed to interpret the discrepancies in various findings, which may be due to the relative sensitivity of various cognitive tests. Third, there are challenges to interpret the findings when using z‐scores—primarily, the loss of meaningfulness of the raw score and its standard deviation, magnifying small changes, not reflecting the reality of memory declines [36].…”
Section: Discussionmentioning
confidence: 99%
“…8,9,12 Thus, we may be underpowered to detect change with the smaller sample size with both Aβ and tau imaging using this EF composite. 8,9,12 Thus, we may be underpowered to detect change with the smaller sample size with both Aβ and tau imaging using this EF composite.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker‐based point prediction of cognitive decline is, thus, a challenge to sufficiently power clinical trials via risk enrichment and to identify subjects at imminent risk of cognitive deterioration. Previous studies have shown that higher amyloid‐PET, 11,12 MRI‐assessed hippocampal atrophy, 13 FDG‐PET hypometabolism, 12 and tau levels 14,15 are associated with faster cognitive decline. Because biomarker combinations can enhance the accuracy for predicting clinical progression, 16 a critical yet unresolved question is how to merge multimodal and increasingly complex (eg, voxel‐wise PET and MRI) data to maximize the prediction accuracy while keeping the number of assessments and costs low.…”
Section: Introductionmentioning
confidence: 97%